Genome-wide association study reveals novel genetic markers associated with endurance athlete status - Al-Khelaifi, F.; Yousri, N.; Albagha, O.; Semenova, E. A.; Kostryukova, E.; Kulemin, N. A.; Borisov, O. V.; Andryushchenko, L. B.; Larin, A. K.; Generozov, E. V.; Donati, F.; Botrè, F.; et al. (2019)
Background: The genetic predisposition to elite athletic performance has been a controversial subject due to the underpowered studies and the small effect size of identified genetic variants. The aims of this study were to investigate the association of common single-nucleotide polymorphisms (SNPs) with endurance athlete status in a large cohort of elite athletes using GWAS approach, followed by a functional validation of significant SNPs by metabolomics analysis. Results: The association of 476,728 SNPs of Illumina DrugCore Gene chip and endurance athlete status was investigated in 753 European international-level athletes (594 males, 159 females) by comparing allelic frequencies between athletes specialized in sports with high (n=630) and low/moderate (n=123) aerobic component. Validation of results was performed by comparing the frequencies of the most significant SNPs between 176 elite Russian endurance athletes and 173 Russian controls or 43 sprinters. Two novel SNPs showed significant associations with endurance athlete status at Bonferroni level of significance (rs56330321 in ATP2B2, p=1.46E-7) and FDR level of significance (rs2635438 in SYNE1, p=2.54E-7), respectively. Replication study using Russian cohorts and a subsequent meta-analysis have confirmed the association of rs56330321 and rs2635438 SNPs with endurance athlete status at genome-wide significance (P= 5.13E-09 and 1.91E-08, respectively). Metabolomics analysis revealed several amino acids and lipids associated with the identified SNPs with potential roles in performance enhancement. Conclusions: This is the first report of GWAS significant SNPs and related metabolites associated with elite athlete status. Further investigations of the functional relevance of the identified SNPs and metabolites in relation to enhanced athletic performance are warranted.